What Are the Precursor and Early Lesions of Peripheral Intrahepatic Cholangiocarcinoma? - Yasuni Nakanuma; Akemi Tsutsui; Xiang Shan Ren; Kenichi Harada; Yasunori Sato; Motoko Sasaki (International Journal of Hepatology)
Cholangiocarcinoma (CC) is divided into distal, perihilar, and intrahepatic CCs (ICCS), and are further subdivided into large bile duct ICC and peripheral ICC. In distal and perihilar CC and large duct ICC, biliary intraepithelial neoplasm (BilIN) and intraductal papillary neoplasm (IPN) have been proposed as precursor lesions. Peripheral ICC, bile duct adenoma (BDA), biliary adenofibroma (BAF), and von Meyenburg complexes (VMCs) are reportedly followed by development of ICCs. Herein, we surveyed these candidate precursor lesions in the background liver of 37 cases of peripheral ICC and controls (perihilar CC, 34 cases; hepatocellular carcinoma, 34 cases and combined hepatocellular cholangiocarcinoma, 25 cases). In the background liver of peripheral ICC, BDA and BAF were not found, but there were not infrequently foci of BDA-like lesions and atypical bile duct lesions involving small bile ducts (32.4% and 10.8%, resp.). VMCs were equally found in peripheral CCs and also control CCs. In conclusion, BDA, BAF, and VMCs are a possible precursor lesion of a minority of peripheral CCs, and BDA-like lesions and atypical bile duct lesions involving small bile ducts may also be related to the development of peripheral ICC. Further pathologic studies on these lesions are warranted for analysis of development of peripheral ICCs.